Maloclusión dental relacionada con la postura corporal. - Ulloa Lopez, Monserrath Estefania (2024)
The present research aims to analyze dental malocclusion and its relationship with body posture through a literature review, using a descriptive and documentary non-experimental approach, based on information from the last 5-10 years. Selection criteria were established, excluding unrelated information. Various databases such as PubMed, SciELO, Medigraphic, and Google Scholar are utilized, along with keywords in the bibliographic search. The results demonstrate the mutual influence between malocclusion and body posture, highlighting their impacts on oral and systemic health. Furthermore, there is a need for comprehensive preventive and therapeutic interventions considering both dimensions, where the structural and functional connection between the jaw, cervical spine, and masticatory muscles is explored, emphasizing the importance of addressing both conditions simultaneously. Published findings support that during childhood and adolescence, individuals are more susceptible to developing malocclusions. Similarly, the association between Class II and Class III malocclusions and postural alterations, especially in the craniocervical region, where Class II patients tend to advance the position of the head, this causes an increase in the tension of the dorsal muscle chains. and a hyperextension of the ventrals, leading to contraction of the supra- and infrahyoid muscles resulting in an increase in cervical lordosis; while, in Class III there is an increase in the activity of the prevertebral muscles, which results in a verticalization of the cervical spine and the loss of its normal lordosis. This leads to an increase in tension in the infra and suprahyoid muscles, causing the individual to tend to look down and have flat plantar support with the hindfoot valgus.